Knowledge ,attitude and practice of voluntary counseling and testing (VCT) for HIV/AIDS amongst the health professionals in Umpumulo Hospital , Mapumulo , Ilembe District , Kwazulu-Natal Province - Obiajulu, Anthony (University of Limpopo (Medunsa Campus), 2009)
The impact of HIV/AIDS on the health sector and the health professionals that work in it is huge. This impact has contributed to the continuing attrition of health professionals in South Africa. Voluntary Counseling and Testing (VCT) has a central role to play in the response to these problems both at the level of the health sector in general and most especially at the level of the individual health professional. Thus, understanding factors that affect the practice of VCT amongst this group of professionals is crucial in South Africa‟s quest to reverse these negative trends. AIM The aim of this study was to determine the level of knowledge, to access and understand the attitude and practice of VCT for HIV/AIDS amongst the health professionals in a rural district Hospital and to make recommendations in order that appropriate intervention strategies may be instituted. METHODS A descriptive cross-sectional quantitative study design was used in which data was collected using a self-administered questionnaire. The study population included all the health professionals working in the hospital at the time of the study but excluded those who were on leave or absent from duty during the period of data collection. Informed consent was obtained from each participant. Data was captured and analyzed using the SPSS version 15.0 (SPSS Inc, Chicago, Illinois, USA). vi RESULTS There was a very high level of knowledge, a moderately supportive attitude and a moderately high level of practice of VCT amongst the study participants. Divorced/separated respondents to this study had more supportive attitude towards VCT than their single colleagues. Age was found to have a very weak but positive correlation to attitude score. There was no significant difference in knowledge and attitude scores between those who practiced VCT and those who did not. CONCLUSION Health professionals understand the importance of VCT as an HIV preventive behavior but there remains some VCT knowledge, attitude and practice concerns together with other determinants of VCT behavior that needs to be addressed.
Thesis(M Med.(Family Medicine)--University of Limpopo, 2009.
Keywords: Voluntary Counseling; HIV AIDS; Testing (VCT)